Molecular Docking of Avocado Leaf (Persea americana) Chemical Compounds againts Angiotensin Converting Enzyme - Alyavayza Putri Monoarfa; Rizky Resvita R Bahi; Moh. Rivaldi Mappa (Journal of Experimental and Clinical Pharmacy (JECP), 2026)
Angiotensin-Converting Enzyme (ACE) plays a key role in the pathogenesis of hypertension by converting angiotensin I into the vasoconstrictive angiotensin II. Avocado leaves (Persea americana) are known to exhibit antihypertensive activity through ACE inhibition, comparable to that of captopril. However, the molecular interaction of compounds identified in avocado leaves with ACE has not been extensively investigated in silico. This study aimed to explore the molecular mechanisms of identified compounds in avocado leaves in inhibiting ACE through molecular docking analysis. Docking simulations were performed between the identified compounds and the ACE protein target (PDB ID: 1O86). The compounds were identified from preliminary studies and screened for potential biological activity using PASS Online. Out of 19 compounds screened, 14 showed predicted antihypertensive activity. The best docking results were observed for trans-tiliroside (ΔG –8.39 kcal/mol), quercitrin (ΔG –8.32 kcal/mol), and ficumegasoside (ΔG –8.26 kcal/mol). These three compounds demonstrated strong binding affinity towards ACE, indicating their potential as natural ACE inhibitors. The findings suggest that trans-tiliroside, quercitrin, and ficumegasoside could serve as promising candidates for the development of antihypertensive therapies derived from natural products.